Les garanties légales relatives aux automobiles neuves et d'occasion - Rousseau-Houle, Thérèse (Les Cahiers de droit, 1982)
As a result of the very wide use of conventional warranties offered by manufacturers and dealers, the Civil Code's provisions on legal warranty have, in the case of new and used cars sales, long been neglected. The Consumer Protection Act has introduced, for the sale of new cars, legal standards of warranty regarding eviction and latent defects, standards which can in no way be diminished or excluded by the parties. The Act also prescribes a new set of warranties for the sale and repair of used cars. Today, the buyer is therefore entitled to the double protection offered by the Code and the Act.